2018
DOI: 10.1002/smll.201802349
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite/Organic Bulk‐Heterojunction Integrated Ultrasensitive Broadband Photodetectors with High Near‐Infrared External Quantum Efficiency over 70%

Abstract: Ultraviolet-visible-near infrared (UV-Vis-NIR) broadband detection is important for image sensing, communication, and environmental monitoring, yet remains as a challenge in achieving high external quantum efficiency (EQE) in the broad spectrum range. Herein, sensitive broadband integrated photodetectors (PDs) with high EQE levels are reported. The organic bulk-heterojunction (OBHJ) layer, based on a NIR sensitive organic acceptor, is employed to extend the response spectrum of the perovskite PDs. A key strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 65 publications
1
47
0
Order By: Relevance
“…Organic-inorganic hybrid perovskites (OIHPs) are emerging materials that have been progressively enabling new thin-film optoelectronics, including solar cells [21][22][23][24][25][26][27] , light-emitting diodes 28,29 and photodetectors 14,16,[30][31][32][33][34][35][36] . The extensive application of hybrid perovskites can be attributable to their excellent optical and electrical properties, including a direct bandgap, large absorption coefficient, high carrier mobility, and low trap density [37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic-inorganic hybrid perovskites (OIHPs) are emerging materials that have been progressively enabling new thin-film optoelectronics, including solar cells [21][22][23][24][25][26][27] , light-emitting diodes 28,29 and photodetectors 14,16,[30][31][32][33][34][35][36] . The extensive application of hybrid perovskites can be attributable to their excellent optical and electrical properties, including a direct bandgap, large absorption coefficient, high carrier mobility, and low trap density [37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the detection range of MAPbI 3 (either polycrystalline films or thin single crystals) is limited to the wavelength region below 820 nm and does not cover the near-infrared (NIR) range, which severely limits its application, especially in biomedical imaging. To overcome this problem, an advantageous strategy has been demonstrated: combining OIHP and an organic bulk heterojunction (BHJ) consisting of donor-acceptor materials with light absorption in the NIR region 16,35,36,42 . Shen et al reported a composite photodetector based on MAPbI 3 and PDPPTDTPT/PCBM, which exhibited a wider detection wavelength extending to 950 nm with a 5 ns ultrafast response time 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [92] Copyright 2018, Wiley-VCH. g) Absorption spectra of different films by spin coating, the inset is the chemical structures of F8IC and PTB7-Th and h) EQE curves of the IPD, pure perovskite and pure BHJ devices at zero bias.…”
Section: Multilayered Strategy Based Broadband Pd-opdsmentioning
confidence: 99%
“…The detectivity D* is one of the key parameters of a PD, which usually describes the ability to detect weak signals. The photoresponsivity is calculated by Equation 2 [3]: (2) where R, S, q, and I dark represent responsivity, illuminated area, electronic charge, and dark current, respectively. The calculated detectivity D* of our device is as high as 10 13 Jones.…”
Section: Preparation and Characterization Of The Flexible Pdsmentioning
confidence: 99%
“…Full-spectrum photodetectors (PDs) that can detect light from ultraviolet to near-infrared have attracted widespread attention in recent years for a variety of applications in industry and technology, such as optical sensing/communication, environmental monitoring, biomedicine, and the "internet of things" [1][2][3][4]. Especially full-spectrum PDs applied in flexible wearable elec-tronic devices have been extensively researched [5].…”
Section: Introductionmentioning
confidence: 99%